Science Fiction and Its Relationship to Beyond Memory in Kindergarten Children - Al-Jubouri, Raghda K. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the meta-memory and science fiction levels and the relationship between them for the kindergarten children. The scales which are prepared by the researchers are used based on Falafel theory (2000) in the case of meta-memory in the case of science fiction. The number of paragraphs of the meta- memory scale are (40). The verification had been obtained for the psychometric properties of the two utilized tools. The meta-memory and science fiction scales had been applied to a sample of kindergarten children/ pre-primary grade of (200) children randomly selected. The results showed that there were statistically significant differences between the average sample scores and hypothetical average of the scale. This difference is favor for the average sample scores, which confirms that the kindergarten children are characterized by science fiction and meta- memory. The differences in the relationship between science fiction and meta-memory for kindergarten children are resulting from the gender variable. The results also approved that there is a positive relationship between science fiction and meta-memory for kindergarten children.